Wyrok Rafała Wojaczka jako kres możliwości podmiotu - Pertek, Grzegorz (Poznańskie Studia Polonistyczne. Seria Literacka, 2012)
The present article attempts to interpret the poem Wyrok [The Verdict] written by Rafał Wojaczek. The author tries to reveal the rules of the game in the play with psychoanalysis that are set in motion in the poem by the introduction of the Freudian signature to the text. Citing the Oedipus complex as one of the “representative” mechanisms for the development of the phenomenon of unawareness, he proceeds to prove that the theory of psychoanalysis as the interpretative context can function on the principle of the paradox, i.e. the stronger the denial of it within the subject, the more important it becomes for the understanding of the work. In this way, Wojaczek, by making the poem heretically sealed, opens it up to interpretation and, eventually, implies that its sense goes beyond any explanation (negation of psychoanalysis as an interpretative method). This last statement makes the basis for a formulation of further assumptions on the psychical structure of the subject (conscious unawareness and unconscious awareness), as well as the relations between the author, the subject and the lyrical protagonist where the author, after exceeding the limits of the poem, splits himself into two instances: textual representation (that of the father) and the lyrical “I” that is the irrevocable verdict condemning the poet to making them fit into language and grammar. An attempt, then, at salvation and a coupling of the body (blood) with the lingering word turns out, however, to be deadly, a carrying out of the verdict.